Synergistic Effect of Potassium Iodide on Inhibitive Performance of Propyl Alcohol during Corrosion of Mild Steel in 1.0M HCl - Yaro, Aprael. S.; Abdul Majeed, Basma A.; Atiyah, Elaf Q. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The inhibition of mild steel corrosion in 1.0M HCl by 1-propanol and the synergistic effect of potassium iodide (KI) was investigated using weight loss and polarization techniques in the temperature range (30 ‒ 50) ̊ C. A matrix of Doelhert to three factors was used as the experimental design, adopting weight loss results as it permits the use of the response surface methodology which exploited in determination of the synergistic effect as inhibition on the mild steel. The results were confirmed using electrochemical polarization measurements. Experimental results showed that the inhibition efficiency (IE%) increases with increase in concentration of inhibitor and with increasing of temperature. The addition iodide ions to alcohol (inhibitor) enhanced the inhibition eﬃciency due to synergistic eﬀect. Potentiodynamic polarization studies showed that the studied compound is mixed-type inhibitor causing blocking of active sites on the mild steel surface .The adsorption of  the inhibitor and its combination with iodide ions on mild steel surface followed       Langmuir adsorption isotherm via physisorption mechanism, which was proposed based on values of adsorption Gibbs free energy difference ΔGads. Statistically, the multi-variable regression equation describes the behavior of the corrosion inhibition process with high accuracy (correlation coefficient R2 between 0.974 and 1).